Urinary tract infection in children - short versus standard duration antibiotic therapy - Namroży, Natalia; Dubel, Robert; Czekaj, Aleksandra; Ruszel, Kinga; Dubel, Julia; Merkisz, Konrad; Nemeczek, Sylwia; Grzybowski, Jakub; Jaskuła, Karolina; Orłowski, Władysław (Journal of Education, Health and Sport, 2022)
Background: Urinary Tract Infection (UTI) is a common infection in children. Prompt diagnosis and appropriate treatment are very important to reduce the morbidity. Pediatric urologists are now faced with a situation that requires appropriate action- antibiotic resistance of urinary tract pathogens is significantly increasing worldwide. Objective: The purpose of our work is to present the clinical aspects of antibiotic use in pediatric urology. To present the benefits of both short antibiotic therapy and standard antibiotic therapy. Methods and materials: A literature review was conducted in the PubMed database, using the key words: "urinary tract infection", "children", "short-term antibiotics", "antibiotics", „nephrology”. Results: Short-term antibiotic therapy for lower urinary tract infections appears to be as effective as standard therapy. Studies show that shorter antibiotic therapy also works well for pyelonephritis in pediatric patients. Children who have received a short course of antibiotic therapy may also be less likely to get subsequent infections in the future with a more resistant strain of the same uropathogen. Conclusion: Tried to reconcile the latest reports on diagnosis, treatment and follow-up in pediatric UTIs with existing practice and opinions on the use of short as well as standard antibiotic therapy. However, more clinical trials are needed to confirm efficacy, and to assess side effects of the therapy